2016
DOI: 10.2993/0278-0771-36.2.348
|View full text |Cite
|
Sign up to set email alerts
|

How do Artisanal Fishermen Name Fish? An Ethnotaxonomic Study in Northeastern Brazil

Abstract: Ethnotaxonomy seeks to understand how people identify, name, and classify living organisms, associating traditional and scientific knowledge. We examined the ethnobiological and ethnotaxonomic classification systems of fishermen in relation to naming commercial fish at the Tamandaré and Batoque beaches on the northeastern coast of Brazil. Seventy-five fishermen were interviewed between January and August of 2013. The interviews concentrated on the morphological, ecological, and sociocultural criteria used in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 37 publications
1
5
0
2
Order By: Relevance
“…In this study, different species belonging to the same genera were commonly identified as a single folk species (e.g., Rhizoprionodon lalandii and R. porosus were both named cação rabo-seco ). The fact that fishers may find it difficult to identify shark species belonging to the same genus has been suggested before for Brazil [ 41 , 42 ], and it is probably related to the high morphological similarity between close species. The difficulty in identifying sharks to species level is also observed in the official fisheries statistics, where sometimes even species not so closely related are grouped together.…”
Section: Discussionmentioning
confidence: 93%
“…In this study, different species belonging to the same genera were commonly identified as a single folk species (e.g., Rhizoprionodon lalandii and R. porosus were both named cação rabo-seco ). The fact that fishers may find it difficult to identify shark species belonging to the same genus has been suggested before for Brazil [ 41 , 42 ], and it is probably related to the high morphological similarity between close species. The difficulty in identifying sharks to species level is also observed in the official fisheries statistics, where sometimes even species not so closely related are grouped together.…”
Section: Discussionmentioning
confidence: 93%
“…O mesmo foi observado por Begossi e Figueiredo (1995) em Búzios (RJ), Seixas e Begossi (2001) em Ilha Grande (RJ), Clauzet et al (2007) em Valença (BA) e Pinto et al (2016) em Tamandaré (PE). Os nomes genéricos ou monomiais podem ser monotípicos quando são únicos, ou seja, não há divisões específicas, ou politípicos quando há diferenciações específicas.…”
Section: Resultsunclassified
“…Alguns estudos demonstraram que os nomes genéricos compostos e os binominais podem ser resultantes de analogias a animais, objetos, lugares, e até características ecológicas de habitat (MOURÃO e NORDI, 2003;RAMIRES et al, 2012). No município de Macaé, a espécie Pleoticus muelleri (Bate, 1888), conhecida popularmente no Uruguai e Argentina como "lagostino" e "lagostin", e no Brasil como "lagostinho da Argentina", "camarão vermelho", "camarão ferro" e "camarão barbado", é chamada localmente de "camarão Santana", em referência ao Arquipélago de Santana, localizado a aproximadamente 6 km da costa do município de Macaé, região onde a espécie é muito abundante segundo os pescadores locais.…”
Section: Resultsunclassified
“…We recognize that this sample size does not allow us to check within community variation on fish names or recurrent names consistently assigned to some fish species through binomials (Begossi et al 2008). A large sample size could also allow a better evaluation of correspondences between local names (ethnospecies) and scientific names (Previero et al 2013;Pinto et al 2016). However, despite this limited sample size, the interviewed fishers still recognized and named most fish species in the Negro River and all fish species in the Tapajos River, thus even a few experienced fishers could provide useful and detailed information on fish biodiversity.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, fishers' knowledge has provided many useful and new data on fish ecology including reproduction, trophic interactions, distribution, migration, invasive species, temporal trends in abundance or size, and interactions with aquatic mammals (Silvano et al 2006;Silvano and Valbo-Jørgensen 2008;Le Fur et al 2011;Turvey et al 2013;Pont et al 2016;Lopes et al 2019;Santos et al 2020;Araujo Catelani et al 2021;Ribeiro et al 2021). Furthermore, ethnobiological studies on how fishers name and classify fish have provided relevant information to improve fisheries monitoring and collaboration between fishers and biologists in small-scale coastal fisheries (Begossi and De Figueiredo 1995;Paz and Begossi 1996;Seixas and Begossi 2001;Freire and Pauly 2005;Begossi et al 2011;Previero et al 2013;Pinto et al 2016;Carvalho et al 2018).…”
Section: Introductionmentioning
confidence: 99%